Mythological Spirit of Riau Malayan Islamic Culture as Reflected on Visual Artifacts - Pujiyanto, Pujiyanto; Abdul Majid, Roshida (KnE Social Sciences, 2023)
Culture refers to human knowledge as social creatures used to understand, create, and interpret his experience and environment and embody the basic framework creating and encouraging the creation of behavior useful to a State’s culture. Culture that spreads throughout archipelago underlies and characterizes an attempt of raising a certain region to be a city or a region’s benchmark. Similarly, Riau city is the Malayan cultural center, with the majority of Muslim populations still maintaining and developing their sharia. Departing from this fact, research is conducted on the visual artifact of Riau Malayan culture with Islamic characteristics inherent to the elements supporting the traditional house (rumah adat). Viewed from the visual artifacts supporting this traditional house, there are some ornaments in the form of vines (flora creeping or climbing along a surface). To discover the product of Riau culture, a study is conducted with visual artifacts constituting the supporting elements and the ornaments of traditional house being the main object. The research was conducted through observing and interviewing and a document study was conducted on the old manuscripts and ornaments stored in the museum of Sang Nila Utama Riau Province. The data obtained from various sources were than validated using the triangulation method and then analyzed using Clive Bell’s esthetic approach, “meaningful shape”. The analysis was concentrated on the cultural mythology of Riau community, majority of who are Muslims, so that their kinship’s social relation reflects Islam sharia. The result shows that visual cultural artifacts in the form of traditional house ornaments created by Riau people lead to human life and moral messages for human beings to socialize with His fellow creature, to obey His instruction, and to keep close to God who gives life and provides welfare. Keywords: Riau, artifact, ornament, mythology, social-cultural